Modelização gráfica da Pré-História do Rio Grande do Sul: Os sítios arqueológicos ameríndios, culturas e temporalidades - Danilo Alexandre Galhardo; Juliana Aparecida Rocha Luz Zago; Thiago Moraes Passos; David Lugli Turtela Pereira (Confins)
This article worked with data from archaeological sites dating from different Amerindian cultures – archaeological traditions – in the state of Rio Grande do Sul (Southern Brazil), collected from archaeological synthetic works. The systematization of these data allowed the production of thematic maps (produced in ArcGIS version 10.2) and schemes based on the graphical modelling method, understood as an “instrument for regional analysis” (THÉRY, 2004). Thus, the corematic supported by different archaeological studies developed in the country, the locations of the cultural contexts and their absolute dating, could yield hypotheses on the flows and stays in the territory.